2004
DOI: 10.17221/5726-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water reuse system on antioxidant enzymes of rainbow trout (Oncorhynchus mykiss w., 1792)

Abstract: ABSTRACT:The objective of the present study was to investigate the importance of the antioxidant enzymes; glucose-6-phosphate dehydrogenase (G6PD), glutathione reductase (GR), superoxide dismutase (SOD), glutathione peroxidase (GP) and catalase (CAT) in defense against toxic reactive oxygen species (ROS). For this purpose, comparative studies were performed on the antioxidant enzyme activities in red cells of rainbow trout (Oncorhynchus mykiss) between flow-through and recirculated breeding systems G6PD, GR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…These enzyme systems have been proposed as biomarkers of reactive oxygen species (ROS) mediating contaminant exposure and as a potential tool in environmental risk assessment (Kohen and Nyska 2002;Livingstone 2001). The ROS are detoxified by a set of antioxidant enzymes that protect macromolecules such as proteins, lipids and nucleic acids against damage (Lushchak et al 2001;Ozmen et al 2004). Several studies revealed that exposure to contaminants, including Cd, in aquatic ecosystems can enhance the intracellular formation of ROS which could cause oxidative damage to biological systems (Ercal et al 2001;Ferreira et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzyme systems have been proposed as biomarkers of reactive oxygen species (ROS) mediating contaminant exposure and as a potential tool in environmental risk assessment (Kohen and Nyska 2002;Livingstone 2001). The ROS are detoxified by a set of antioxidant enzymes that protect macromolecules such as proteins, lipids and nucleic acids against damage (Lushchak et al 2001;Ozmen et al 2004). Several studies revealed that exposure to contaminants, including Cd, in aquatic ecosystems can enhance the intracellular formation of ROS which could cause oxidative damage to biological systems (Ercal et al 2001;Ferreira et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized glutathione (GSSG) should be reduced to GSH by the ancillary flavor-enzyme glutathione reductase, which uses NADPH as electron donor (Hasspieler et al 1994). SOD is the enzyme that catalyzes the dismutation of the superoxide anion to O 2 and H 2 O 2 , and CAT reacts with H 2 O 2 to form water and oxygen molecule (Livingstone 2001;Lushchak et al 2001;Ozmen et al 2004). The GPx detoxifies H 2 O 2 or organic hydroperoxides that produced in LPO (Halliwell and Gutteridge 1999).…”
Section: Introductionmentioning
confidence: 99%
“…When statistically examined the effect of application, species and application x species interaction on GR is found to be insignificant. The effects of recirculation system on antioxidant enzymes of rainbow trout and when GR enzyme is compared with control group the result were found very important (Ozmen et al, 2004). Compared with control group for catalase enzyme, the values obtained by application of phenoxyethanol with brown trout are close to normal, but lower in rainbow trout.…”
Section: Resultsmentioning
confidence: 85%
“…G6PD activity changes depending on nutrition, hormones and especially NADPH concentration. Ozmen et al, 2004 inspected the effects of recirculation system on antioxidant enzymes of rainbow trout and when G6PD enzyme is compared with control group the result were found very important. In the application groups, a significant increase was observed in G6PD enzyme activity as it stops the enzyme synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation (LPO) as induced by heavy metal pollution in aquatic organisms is expressed by malondialdehyde (MDA) formation, which represents the secondary LPO product in the thiobarbituric acid reactive substances (TBARS) test (Draper et al 1993). ROS are detoxified as antioxidant defense systems including antioxidants like reduced glutathione and a set of antioxidant enzymes such as glutathione peroxidase, glutathione-S-transferase, superoxide dismutase, and catalase that protect macromolecules against oxidative damage (Ozmen et al 2004). Exposure to contaminants, including Cd, in aquatic ecosystems can enhance intracellular formation of ROS, which could cause oxidative damage to biological systems (Ferreira et al 2005).…”
Section: Introductionmentioning
confidence: 99%